FUNGSI MAMAK DALAM MENJAGA KESEJAHTERAAN EKONOMI PADA MASYARAKAT NAGARI TALUAK KECAMATAN LINTAU BUO - Nanda Annisa; Jamurin; Indra Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the function of mamak in the implementation of adat, identify the challenges and obstacles faced by mamak, and analyze how mamak maintain Minangkabau cultural values and traditions amidst social change. This study used a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Informants included mamak as customary leaders and nephews as subjects who receive the influence of mamak's functions. The results show that the role of mamak in the economic, educational, religious, and customary fields has declined. Many mamak are no longer active in guiding their nephews due to personal busyness, limited distance, and the influence of modernization. Nevertheless, some mamak still maintain their customary role in ceremonies and family decision-making. However, the influence of biological fathers is now more dominant than that of mamak in the lives of their nephews and nieces. The discussion indicates that this shift in roles is a result of rapid sociocultural changes, including increased formal education, migration, and the use of technology. To maintain adat, a revitalization of the role of mamak is needed through a contextual and adaptive approach to current developments.